When Threat Is Near, Get Out of Here: Dynamics of Defensive Behavior During Freezing and Active Avoidance. (November 2015) - Löw, Andreas; Weymar, Mathias; Hamm, Alfons O.
When detecting a threat, humans and other animals engage in defensive behaviors and supporting physiological adjustments that vary with threat imminence and potential response options. In the present study, we shed light on the dynamics of defensive behaviors and associated physiological adjustments in humans using multiple psychophysiological and brain measures. When participants were exposed to a dynamically approaching, uncontrollable threat, attentive freezing was augmented, as indicated by an increase in skin conductance, fear bradycardia, and potentiation of the startle reflex. In contrast, when participants had the opportunity to actively avoid the approaching threat, attention switched to response preparation, as indicated by an inhibition of the startle magnitude and by a sharp drop of the probe-elicited P3 component of the evoked brain potentials. These new findings on the dynamics of defensive behaviors form an important intersection between animal and human research and have important implications for understanding fear and anxiety-related disorders.